Renal Biomarkers in Companion Animals—A Review - Ana Filipa Pereira; Catarina Jota Baptista; Ana Faustino-Rocha; Paula A. Oliveira; Ana Cláudia Coelho (Animals)
Recent advancements in molecular biology have led to the discovery of potential biomarkers for the diagnosis of acute kidney disease (AKD) and chronic kidney disease (CKD). The use of multiple biomarkers in the diagnosis of kidney disease has the potential to enhance both specificity and sensitivity, enabling early detection and intervention that could ultimately reduce morbidity and mortality rates. This review provides an overview of studies on urine and blood biomarkers and examines their utility and significance in various clinical settings. Further and continuous research is needed to support the application of these biomarkers in clinical practice to facilitate early diagnosis, guidance for different interventions, and the monitoring of disease progression.